2013
DOI: 10.7705/biomedica.v33i3.1631
|View full text |Cite
|
Sign up to set email alerts
|

Diez años de eficacia terapéutica de la cloroquina en malaria no complicada por Plasmodium vivax, Turbo, Antioquia, años 2002 y 2011

Abstract: Eficacia terapéutica de cloroquina en P. vivax Colombia Contribución de los autores:Alexandra Ríos: hizo el trabajo de campo, analizó los resultados y elaboró el manuscrito. Gonzalo Álvarez: hizo los análisis estadísticos y elaboración del manuscrito. Silvia Blair: formulación, dirección del proyecto de investigación y revisión del manuscrito. Palabras clave: cloroquina/uso terapéutico, eficacia, malaria, Plasmodium vivax, Colombia. ARTÍCULO ORIGINAL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…Cases have also been reported in Ethiopia in Africa (6)(7)(8)(9)(10)(11)(12) and in Guyana, Brazil, Venezuela, Peru, and Colombia in South America (13)(14)(15)(16)(17). In Colombia, whereas one study reported the therapeutic failure of chloroquine in 11% (3/27) of the patients evaluated (17), other studies reported 100% efficacy for this antimalarial (14,18). Therefore, the in vitro susceptibility profile of P. vivax to antimalarials must be determined.…”
mentioning
confidence: 93%
“…Cases have also been reported in Ethiopia in Africa (6)(7)(8)(9)(10)(11)(12) and in Guyana, Brazil, Venezuela, Peru, and Colombia in South America (13)(14)(15)(16)(17). In Colombia, whereas one study reported the therapeutic failure of chloroquine in 11% (3/27) of the patients evaluated (17), other studies reported 100% efficacy for this antimalarial (14,18). Therefore, the in vitro susceptibility profile of P. vivax to antimalarials must be determined.…”
mentioning
confidence: 93%
“…La respuesta terapéutica adecuada de la monoterapia con CQ sucedió en 95,8 % de las embarazadas para curar su ataque agudo de malaria vivax no complicada, esto concuerda con un trabajo previo en la misma zona en mujeres gestantes (1) y con otros resultados en población no gestante de este país (20,33,34). En Colombia, tres estudios publicados en 2001-2008, en población no gestante, registraron falla terapéutica de la monoterapia con CQ de 4,2 % (promedio de tres procedimientos de medición) (19), 5 % (35) y 12 % (36), para un promedio bruto de 7,1 %.…”
Section: Discussionunclassified
“…En Colombia, tres estudios publicados en 2001-2008, en población no gestante, registraron falla terapéutica de la monoterapia con CQ de 4,2 % (promedio de tres procedimientos de medición) (19), 5 % (35) y 12 % (36), para un promedio bruto de 7,1 %. Contrario a esto, otros cinco trabajos (de 2001-2013), hallaron eficacia de 100 % de la CQ (1, 20,34). En otros tres trabajos colombianos, en población no gestante, se suministraron simultáneamente CQ y PQ desde el día 1 de tratamiento y en ambos hubo curación del ataque agudo en 100 %.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…20,21 Reported cases of TF with CQ alone in South America suggest that it is necessary to monitor the clinical and parasitological response to the drug because of a possible unrecognized emergence of resistant P. vivax strains in Colombia, although the extent of the threat to national malaria control efforts remains to be determined. In Colombia, the initial studies between 1998 and 2011 found a 100% ACPR to CQ alone in patients with malaria vivax monoinfection [22][23][24][25][26] ; one study reported an 11% rate of TFs in 2001, defined by the authors as "clinical drug resistance" 27 ; and one study addressed P. vivax in vitro susceptibility to various drug regimens between 2010 and 2012. 28 For the last 10 years, no national data were found on P. vivax response to standard treatment in relation to blood drug levels; there is a lack of information on the topic.…”
Section: Introductionmentioning
confidence: 99%